The Canadian Electronic Ensemble: Past, Present, and Future: Panel Discussion - Stillwell, Paul; Montgomery, Jim; Jaeger, David; Gale, Emily (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2021)
In this panel discussion Paul Stillwell, Jim Montgomery, and David Jaeger discuss their experiences in the experimental and electroacoustic scenes, including reflections on technologies, collaborators, and tours. Dr. Emily Gale served as moderator. This panel discussion has been edited for clarity.